Soft biomaterials as a substitute for the Nucleus Pulposus - Nabais, João António Pires Miranda (2014)
One of the largest health problems faced worldwide, when evaluated by direct (clinical) as well indirect cost (absenteeism), is the degeneration of the intervertebral disc (IVD) that leads to back pain and, potentially disability and individual´s quality of life decreasing. The intervertebral disc is a mechanical and biological complex structure, formed by a tough outer layer of fibrocartilage called Annulus Fibrosus (AF),which surrounds a soft, elastic and gelatinous core called Nucleus Pulposus (NP). These two structures are completed by two upper and lower encasing layer called Vertebral Endplates (VEP). The degeneration of the IVD is marked by the dehydration of the Nucleus Pulposus, reducing the hydrostatic pressure inside the nucleus, resulting in a loss of capability to support compressive forces, during the active period, and to regain height during the resting period. This situation will compromise the role of shock absorber by the NP and transfers these forces to the AF. This transfer will result in cracks on the AF, deteriorating the IVD, allowing the ingrowth of vessels and nerves. This project was based on the developing a protocol to test suitable NP replacements, in hope to future assessment of discrete mechanical values and characteristics for an NP replacement. For this, Nucleus pulposus samples from goat, encapsulated Hydromed gel denominated “Raviolis” and Chitosan gels, produced via wet route using an ammonium environment, were confined compressed. Chitosan was rheologically tested and swelling capability of all the three type of materials was assessed. Results showed that the Nucleus Pulposus and “Raviolis” have similar mechanical behavior, being able to swell and “build up” hydrostatic pressure after a compression stage, while the Chitosan gel did not showed that ability. Therefore, “Raviolis” are a more suitable candidate to replace the NP than Chitosan gels. It was also observed that confined compression is the key test to perform on any possible candidate to replace the NP.